Ticket to ride: export of proteins to the plasmodium falciparum-infected erythrocyte - Przyborski, Jude M.; Nyboer, Britta; Lanzer, Michael (Molecular microbiology, 2016)
The malaria parasite Plasmodium falciparum exports numerous proteins to its chosen host cell, the mature human erythrocyte. Many of these proteins are important for parasite survival. To reach the host cell, parasites must cross multiple membrane barriers and then furthermore be targeted to their correct sub-cellular localisation. This novel transport pathway has received much research attention in the past decades, especially as many of the mechanisms are expected to be parasite-specific and thus potential targets for drug development. In this article we summarize some of the most recent advances in this field, and highlight areas in which further research is needed.
Gesehen am 27.01.2021